Medical applications of electromagnetic fields - P. , Nagendrareddy; R. , Puviarasi (International Journal of Psychosocial Rehabilitation, 2020)
This will help to find some possible health effects like malaria and caner. Due to these two health issues, like low-intensity non-ionizing electromagnetic fields from the emf, In malaria therapy, the acceleration of a superparamagnetic material, hemotoxic, within the malaria organism can be caused by an incredibly low-strength level magnetic field. This triggers the organism’s death to radical and mechanical injury. Due to this, we have found the main health treatment for cancer. This will be low cost for people to the treatment for the cancer. The low intensity is the main fault in the human body that loses the body weight. The cancer cells are more affected than the normal cells in the body.